Joining materials and articles
Patent Information
- Application Number
- JP2019234447
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2039-12-25
AI Technical Summary
【0015】 本発明により、300℃程度の比較的低温での焼結性を有し、冷熱サイクル前後の接合強度に優れる焼結膜を形成可能な接合材、及び、該接合材を用いた物品を提供することができる。
Smart Images

Figure 0007629685000001 
Figure 0007629685000002 
Figure 0007629685000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a bonding material and an article bonded with the bonding material. [Background technology]
[0002] Conventionally, solder has been used as a bonding material for bonding metal members together, between a metal member and a semiconductor element, or between a metal member and an LED element. In the field of next-generation power electronics, from the environmental consideration perspective, there is a demand for lead-free alternatives to solder for bonding materials for devices such as SiC that can operate at high temperatures, and bonding materials using silver nanoparticles have been proposed. Generally, metal nanoparticles, such as silver nanoparticles, are coated with an organic substance on the particle surface for stabilization, and when the coating material volatilizes and / or decomposes during sintering, the metal nanoparticles sinter together to form a strong metal film. As an example of a bonding material using such silver nanoparticles, Patent Document 1 describes a silver nano bonding paste containing a sintering accelerator, which has excellent application suitability and bonding strength before and after thermal cycles. Patent Document 2 describes a bonding material containing a specific amount of silver fine particles with an average primary particle size of nm size and silver particles with a size of μm size, and containing a specific sintering aid, which can suppress the generation of unsintered parts. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-172728 A [Patent Document 2] JP 2015-225842 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the bonding materials described in Patent Documents 1 and 2 are unable to solve the problems of bonding strength, particularly thermal shock resistance, such as thermal cycle resistance. Regarding the above, it is believed that the joining paste described in Patent Document 1 has an insufficient design of the boiling points of the coating material that coats the metal particles and the solvent, and the gas generated by the evaporation and / or decomposition of the coating material is not smoothly discharged to the outside of the film, but remains inside the film and forms voids (air spaces). Regarding the above, in the bonding material described in Patent Document 2, one metal particle is coated with a kind of fatty acid, so the metal particle coated with the coating material having a low boiling point starts sintering first, and after the coating film hardens, the other metal particle coated with the coating material having a high boiling point sinters, so that the gas cannot be discharged smoothly and many voids are formed inside the film. The formation of voids causes problems such as weakening of the film, lowering of the bonding strength due to a reduction in the contact area with the substrate, and a significant deterioration in thermal shock resistance.
[0005] Therefore, an object of the present invention is to provide a bonding material that has sinterability at a relatively low temperature of about 300°C and is capable of forming a sintered film having excellent bonding strength before and after thermal cycles, and an article using the bonding material. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the embodiments described below, and have thus completed the present invention.
[0007] An embodiment of the present invention relates to a bonding material including metal particles coated with a fatty acid and an organic solvent, in which the fatty acid includes fatty acid A having 4 to 8 carbon atoms and fatty acid B having 14 to 20 carbon atoms, and the organic solvent includes organic solvent C having a boiling point of 170° C. to 230° C. and organic solvent D having a boiling point of 300° C. to 350° C.
[0008] Another embodiment of the present invention relates to the above bonding material, wherein the molar ratio of fatty acid A to fatty acid B (molar number of fatty acid A / molar number of fatty acid B) is 0.5-30.
[0009] Another embodiment of the present invention relates to the above bonding material, wherein the mass ratio of organic solvent C to organic solvent D (mass of organic solvent C / mass of organic solvent D) is 1-3.
[0010] Another embodiment of the present invention relates to the above bonding material, wherein the boiling point of the fatty acid A is a temperature within the range of the boiling point of the organic solvent C ±0 to 20°C.
[0011] Another embodiment of the present invention relates to the above bonding material, wherein the boiling point of the fatty acid B is a temperature within a range of the boiling point of the organic solvent D ±0 to 50°C.
[0012] Another embodiment of the present invention relates to the above-mentioned bonding material, wherein the metal particles are a reduced product obtained by reducing a silver compound using a carbodihydrazide represented by the following formula (1) or a polybasic acid polyhydrazide represented by the following formula (2).
[0013] [ka] [In formula (2), R represents an n-valent polybasic acid residue.]
[0014] Another embodiment of the present invention relates to an article in which metal members are bonded together, a metal member and a semiconductor element, or a metal member and an LED element are bonded together with a sintered body formed from the above-mentioned bonding material. Effect of the Invention
[0015] The present invention can provide a bonding material that has sinterability at a relatively low temperature of about 300° C. and is capable of forming a sintered film that has excellent bonding strength before and after thermal cycles, and an article using the bonding material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The bonding material of the present invention is characterized in that it contains metal particles coated with a fatty acid, the fatty acid including fatty acid A having 4 to 8 carbon atoms and fatty acid B having 14 to 20 carbon atoms, organic solvent C having a boiling point of 170°C to 230°C, and organic solvent D having a boiling point of 300°C to 350°C. As a result of extensive research, the applicant has discovered that in order for volatile components such as fatty acids in the bonding material to be smoothly released outside the film, it is important that the bonding material has a low viscosity during sintering and that the fatty acids volatilize together with the solvent components. The applicant has discovered that by combining two types of fatty acids having specific carbon numbers with two types of organic solvents having specific boiling points, it is possible to form a sintered body that exhibits excellent low-temperature sintering properties and thermal shock resistance while maintaining the stability of the bonding material, and that has excellent bonding strength before and after thermal cycles. The present invention will be described in detail below.
[0017] <Metal particles> The bonding material of the present invention includes metal particles coated with a specific fatty acid. Examples of the metal particles include metal powders such as gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, and platinum, alloys thereof, and composite powders thereof. Examples of the metal particles include fine particles coated with a core and a material different from the core material, specifically, silver-coated copper powder in which the core is made of copper and the surface is coated with silver. The metal particles may be used alone or in combination of two or more kinds.
[0018] The metal particles preferably include metal nanoparticles. The metal nanoparticles are not particularly limited as long as they have an average particle size at the nano level, and are preferably 1 to 200 nm, more preferably 5 to 100 nm, further preferably 8 to 80 nm, and particularly preferably 8 to 50 nm. The metal nanoparticles may be used alone with a specific average particle size, or may be used in combination with a plurality of metal nanoparticles with different average particle sizes. By including metal nanoparticles, the activity of the particle surface increases, and the melting point decreases due to the nano-size effect, making it possible to sinter at a low temperature. In other words, low-temperature sintering makes it possible to lower the temperature when mounting electronic components, thereby reducing thermal stress. Furthermore, when the metal nanoparticles bond together through sintering and increase in size, they exhibit a high melting point equivalent to that of normal-sized metal materials (bulk metal materials), which makes it possible to improve the heat resistance temperature after mounting.
[0019] The content of the metal nanoparticles is preferably 25 to 100 mass%, more preferably 80 to 100 mass%, further preferably 90 to 100 mass%, and particularly preferably 95 to 100 mass%, based on 100 mass% of the metal particles.
[0020] The average particle size of the metal nanoparticles can be the cumulative particle size (D50) value of the volume particle size distribution measured using a Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) For the average particle size of metal particles larger than the metal nanoparticles, the cumulative particle size (D50) value of the volume particle size distribution measured using a laser diffraction particle size distribution measuring device "SALD-3000" manufactured by Shimadzu Corporation can be used.
[0021] <Fatty acid> At least a portion of the surface of the metal particles is coated with a fatty acid including fatty acid A having 4 or more and 8 or less carbon atoms and fatty acid B having 14 or more and 20 or less carbon atoms. Fatty acids refer to carboxylic acids (R-COOH) with one carboxyl group in the molecule that have a chain structure, and include those with a straight-chain structure and those with a branched structure, as well as saturated and unsaturated fatty acids. As will be described later, fatty acids are not only used as raw materials for producing metal particles, but also function well as dispersants that remain near the metal surface even after the metal particles are generated by reduction reaction and help stabilize the fine particles.
[0022] [Fatty acid A with 4 to 8 carbon atoms, fatty acid B with 14 to 20 carbon atoms] Fatty acid A with 4 to 8 carbon atoms provides the effect of low-temperature sintering due to its low-temperature decomposability. When fatty acid A has 4 or more carbon atoms, metal particles are stabilized and aggregation between particles is suppressed. Also, when the number of carbon atoms is 8 or less, decomposability at low temperatures is good and low-temperature sintering properties are excellent. Examples of fatty acids A having 4 to 8 carbon atoms include linear saturated fatty acids, linear unsaturated fatty acids, and branched fatty acids. Examples of linear saturated fatty acids include butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, and octanoic acid. Examples of linear unsaturated fatty acids include crotonic acid and isocrotonic acid. Examples of branched fatty acids include 2-ethylhexanoic acid. As the fatty acid A having 4 to 8 carbon atoms, a straight-chain saturated fatty acid is preferred. A straight-chain fatty acid is preferred because it has excellent lipophilicity, improved stability in non-aqueous solvents, and a low decomposition temperature and excellent low-temperature sinterability. The fatty acid A having 4 to 8 carbon atoms may be used alone or in combination.
[0023] Fatty acid B with carbon number of 14 to 20 mainly provides the effect of stabilizing metal particles. When fatty acid B has carbon number of 14 or more, metal particles are stabilized, aggregation between particles is suppressed, and the viscosity of the bonding material is reduced, resulting in excellent coating suitability. Furthermore, when the carbon number is 14 or more, the affinity of metal particles to non-water-soluble solvents is improved. When the carbon number is 20 or less, the effect of low-temperature sintering is exhibited. Examples of fatty acids B having 14 to 20 carbon atoms include linear saturated fatty acids, linear unsaturated fatty acids, and branched fatty acids. Examples of linear saturated fatty acids include myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, and arachic acid. Examples of linear unsaturated fatty acids include palmitoleic acid, oleic acid, and erucic acid. Examples of branched fatty acids include 2-hexyldecanoic acid. As the fatty acid B having 14 to 20 carbon atoms, a straight-chain unsaturated fatty acid is preferred. A straight-chain unsaturated fatty acid is preferred because it has excellent lipophilicity, improved stability in non-aqueous solvents, and a low decomposition temperature and excellent low-temperature sintering property. The fatty acid B having 14 to 20 carbon atoms may be used alone or in combination. Therefore, by using fatty acid A and fatty acid B in combination, both the stability of the metal particles and the low-temperature sintering property can be achieved, which is preferable.
[0024] The boiling point of fatty acid A is preferably a temperature within ±0 to 20° C. of the boiling point of organic solvent C, and more preferably a temperature within ±0 to 10° C. of the boiling point of organic solvent C. When the boiling point difference is within the range of ±0 to 20° C., an excellent void reduction effect is exhibited. For example, if the boiling point of fatty acid A is too high relative to that of organic solvent C, organic solvent C will volatilize first, causing the inside of the film to become highly viscous, and the volatile components of fatty acid A, which volatilize later, will not be discharged smoothly, causing the volatile components of fatty acid A to remain and form voids. On the other hand, if the boiling point of organic solvent C is too high relative to that of fatty acid A, fatty acid A will volatilize first, and sintering will progress partially, causing the inside of the film to become highly viscous, and the volatile components of organic solvent C, which volatilize later, will not be discharged smoothly, causing the volatile components of organic solvent C to remain and form voids. By setting the boiling point of fatty acid A to a temperature within ±0 to 20°C of the boiling point of organic solvent C, both components volatilize at the same time, maintaining a low viscosity state and allowing the volatile components to be discharged smoothly. This reduces voids.
[0025] The boiling point of the fatty acid B is preferably a temperature within the boiling point of the organic solvent D ±0 to 50°C. For example, if the boiling point of fatty acid B is too high relative to that of organic solvent D, organic solvent D volatilizes first, causing the inside of the film to become highly viscous, and the volatile components of fatty acid B that volatilize later cannot be discharged smoothly, causing the volatile components of fatty acid B to remain and form voids. On the other hand, if the boiling point of organic solvent D is too high relative to that of fatty acid B, fatty acid B volatilizes first, and sintering progresses partially, causing the inside of the film to become highly viscous, and the volatile components of organic solvent D that volatilize later cannot be discharged smoothly, causing the volatile components of organic solvent D to remain and form voids. By setting the boiling point of fatty acid B to a temperature within ±0 to 50°C of the boiling point of organic solvent D, both components volatilize at the same time, maintaining a low viscosity state and allowing the volatile components to be discharged smoothly. This reduces voids.
[0026] The molar ratio of fatty acid A to fatty acid B (molar number of fatty acid A / molar number of fatty acid B) is preferably 0.5-30, more preferably 1-15, and further preferably 2-8. When the molar ratio of fatty acid A and fatty acid B is 0.5 or more, the ratio of fatty acid A, which has excellent low-temperature sinterability, becomes high, and the resulting bonding material has excellent low-temperature sinterability. As described above, fatty acid A volatilizes before fatty acid B due to the difference in carbon number in the sintering process, and the bonding material has a high viscosity at the stage when fatty acid B volatilizes, so the volatile components of fatty acid B tend to remain in the film of the bonding material more easily than fatty acid A, leading to void formation. Therefore, a high ratio of fatty acid A is preferable from the viewpoint of reducing voids in the film formed by the bonding material. It is preferable that the molar ratio of fatty acid A to fatty acid B is 30 or less, since fatty acid B further stabilizes the metal particles.
[0027] The method for determining the molar ratio of fatty acid A and fatty acid B is not particularly limited, but includes a method using pyrolysis GC or pyrolysis GC-MS. Specifically, a powder of metal particles coated with a fatty acid is heated to the boiling point of fatty acid B or higher, and the generated volatile components are introduced into GC or GC-MS for analysis. From the area of the obtained chart, the molar ratio of fatty acid A and fatty acid B can be calculated by quantifying each component using a calibration curve.
[0028] <Production of Metal Particles Coated with Fatty Acids> The method for producing the metal particles coated with fatty acid is not particularly limited, and they can be produced by a known method. Among them, the metal particles coated with fatty acid are preferably reduced metal compounds, more preferably reduced silver compounds using carbodihydrazide represented by the following formula (1) or polybasic acid polyhydrazide represented by the following formula (2).
[0029] [ka] [In formula (2), R represents an n-valent polybasic acid residue.]
[0030] The carbodihydrazide or polybasic acid polyhydrazide functions as a reducing agent, and the reduction reaction may be carried out by either a method in which a liquid medium is mixed with a metal salt compound of a fatty acid and then the carbodihydrazide or polybasic acid polyhydrazide is added to reduce the metal salt compound, or a method in which a liquid medium is mixed with a carbodihydrazide or polybasic acid polyhydrazide and then the metal salt compound of a fatty acid is added to reduce the metal salt compound.
[0031] The liquid medium in which the metal salt compound of a fatty acid is dispersed is not particularly limited. However, in consideration of processes such as the removal of impurities, a non-aqueous solvent that undergoes phase separation from water is preferred, and it is preferable to disperse the metal salt compound of a fatty acid in the non-aqueous solvent and then add an aqueous solution of carbodihydrazide or polybasic acid polyhydrazide, which is a reducing agent.
[0032] As the fatty acid of the metal salt compound of a fatty acid, it is preferable to use the above-mentioned fatty acid A having 4 to 8 carbon atoms and / or fatty acid B having 14 to 20 carbon atoms. The metal capable of forming a metal salt compound of a fatty acid is not particularly limited, but is preferably at least one metal selected from Group VIII and Group IB metals such as gold, silver, copper, nickel, palladium, platinum, iron, cobalt, and mercury, and in consideration of low-temperature sintering, is preferably at least one metal selected from the group consisting of gold, silver, and copper. The metal salt compound of fatty acid can be obtained by a known method, for example, by dissolving a commercially available fatty acid sodium salt or a fatty acid sodium salt obtained by mixing a fatty acid with sodium hydroxide in water in pure water, adding an equal amount of an inorganic salt of a target metal, and filtering the precipitated fatty acid metal salt compound by suction filtration and drying. The inorganic salts of the above metals are not particularly limited, and examples thereof include chlorides such as chloroauric acid, chloroplatinic acid, and silver chloride, nitrates such as silver nitrate, acetates such as silver acetate and copper(II) acetate, perchlorates such as silver perchlorate, sulfates such as copper(II) sulfate, carbonates, silicates, phosphates, etc., and can be appropriately selected according to the desired metal. These inorganic salts of metals may be used alone or in combination of two or more.
[0033] The polybasic acid polyhydrazide represented by formula (2) is not particularly limited, and examples thereof include dibasic acid dihydrazide, tribasic acid trihydrazide, and tetrabasic acid tetrahydrazide. Among them, dibasic acid dihydrazide is preferred because it has good solubility in a solvent, so that the reduction reaction can proceed uniformly, and also has good storage stability.
[0034] Examples of dibasic acid dihydrazide include malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, dodecanoic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, tartaric acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, hexadecanoic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 1,4-naphthoic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, iminodiacetic acid dihydrazide, and itaconic acid dihydrazide.
[0035] Examples of tribasic acid trihydrazides include citric acid trihydrazide, trimellitic acid trihydrazide, nitriloacetic acid trihydrazide, cyclohexanetricarboxylic acid trihydrazide, etc. Examples of tetrabasic acid tetrahydrazide include ethylenediaminetetraacetic acid tetrahydrazide, pyromellitic acid tetrahydrazide, etc.
[0036] Other examples of polybasic acid polyhydrazides include polyacrylic acid polyhydrazide, etc. These polybasic acid polyhydrazides may be used alone or in combination of two or more, and may also be used in combination with the carbodihydrazide of formula (1). In the carbodihydrazide or polybasic acid polyhydrazide, one or more hydrogen atoms may be substituted with a functional group such as a hydroxyl group.
[0037] Considering purification after the reaction, the reducing agent is preferably added as an aqueous solution, and considering solubility in water, the reducing agent is preferably adipic acid dihydrazide, succinic acid dihydrazide, or glutaric acid dihydrazide.
[0038] In the process of dispersing a metal salt compound of a fatty acid in a liquid medium and carrying out a reduction reaction, a sufficient dispersion effect can be obtained for the metal salt compound of the fatty acid or the generated metal microparticles using only the fatty acid derived from the raw material, but if necessary, a compound having a dispersion stabilizing function (hereinafter sometimes referred to as a "dispersant") may be appropriately added. The compound having the dispersion stabilizing function is not particularly limited, but is preferably a compound having one or more functional groups having affinity to metal compounds, such as an amino group, a quaternary ammonium salt, a hydroxyl group, a cyano group, a carboxyl group, a thiol group, or a sulfonic acid group. The functional group may be contained in the main chain of the compound, or in the side chain, or in both the main chain and the side chain. The compound having the functional group is not particularly limited, but is preferably used, for example, an amine compound, a pigment dispersant, a surfactant, a fatty acid, etc. The fatty acid may be the same fatty acid as the fatty acid of the metal salt compound of the fatty acid as the raw material, or may be a different fatty acid.
[0039] The particle size of the metal particles can be appropriately adjusted as necessary, but is preferably 1 to 200 nm, more preferably 5 to 100 nm, further preferably 8 to 80 nm, and particularly preferably 8 to 50 nm.
[0040] In 100% by mass of metal particles coated with fatty acids, the content of the fatty acid A and fatty acid B is preferably 1 to 30% by mass, more preferably 3 to 15% by mass. If the content of the fatty acid is 3% by mass or more, aggregation of the metal particles is further suppressed, and stability is excellent, which is preferable. If it is 15% by mass or less, voids are further reduced, which is preferable.
[0041] <Organic solvent> The bonding material of the present invention contains organic solvent C having a boiling point of 170° C. or more and 230° C. or less, and organic solvent D having a boiling point of 300° C. or more and 350° C. or less. Organic solvent C and organic solvent D having a boiling point within a predetermined range are not only dispersion media for dispersing metal particles, but also important components for smoothly releasing volatile components of fatty acid A and fatty acid B to the outside of the film during sintering and suppressing void formation. Since the boiling point of the organic solvent C is 170°C or more and 230°C or less, the viscosity of the inside of the bonding material is reduced when the fatty acid A volatilizes and is discharged, and voids are reduced. In addition, the boiling point of the fatty acid A having 4 to 8 carbon atoms is close to the boiling point of the organic solvent C, so that both can volatilize efficiently. For the same reason, since the boiling point of the organic solvent D is 300 to 350°C, the viscosity of the inside of the bonding material is reduced when the fatty acid B volatilizes and is discharged, and voids are reduced. In addition, the boiling point of the fatty acid B having 14 to 20 carbon atoms is close to the boiling point of the organic solvent D, so that both can volatilize efficiently. Then, at the completion of sintering, the fatty acid A, fatty acid B, organic solvent C, and organic solvent D are all volatilized and discharged outside the film, forming a film with reduced voids. Furthermore, since fatty acid B volatilizes after fatty acid A is discharged, it is possible to further reduce voids, so it is also important that the upper limit of the boiling point of organic solvent C (230°C) and the lower limit of organic solvent D (300°C) are not too close.
[0042] Examples of organic solvents C having a boiling point of 170° C. or more and 230° C. or less include dipropylene glycol dimethyl ether (boiling point 175° C.), ethylene glycol n-butyl ether acetate (boiling point 188° C.), octanol (boiling point 195° C.), Isopar L (boiling point 199° C.), dihydroterpineol (boiling point 210° C.), diethylene glycol monobutyl ether (boiling point 230° C.), and 2-2 butoxyethoxyethanol (boiling point 230° C.). These organic solvents C can be used alone or in combination as appropriate.
[0043] Examples of organic solvents D having a boiling point of 300° C. or more and 350° C. or less include polyethylene glycol monomethyl ether (boiling point 300° C.), isobornylcyclohexanol (boiling point 318° C.), benzyl benzoate (boiling point 324° C.), and bis(2-ethylhexyl) adipate (boiling point 335° C.). These organic solvents D can be used alone or in combination as appropriate.
[0044] The mass ratio of organic solvent C to organic solvent D (mass of organic solvent C / mass of organic solvent D) is preferably 1 to 3, and more preferably 1 to 2. When the mass ratio is 1 or more, the discharge of the volatile components of fatty acid A to the outside of the film is promoted, and the volatile components of organic solvent D, which has a high boiling point, are prevented from remaining in the film, which is excellent in reducing voids. When the mass ratio is 3 or less, the discharge of the volatile components of fatty acid B to the outside of the film is promoted, which is excellent in reducing voids.
[0045] <Joining material> The bonding material of the present invention contains the above-mentioned metal particles coated with fatty acids, organic solvent C, and organic solvent D. The content of the metal particles coated with fatty acids relative to 100 mass% of the total solid content of the bonding material is preferably 80 mass% or more, more preferably 85 to 99 mass%, and even more preferably 90 to 99 mass%. By containing 80 mass% or more of the metal particles coated with fatty acids, it becomes possible to more firmly bond members to be bonded together, which will be described later.
[0046] The bonding material of the present invention may contain a sintering accelerator. The sintering accelerator is a compound having a functional group with high affinity to metal particles, and due to the high affinity, it has the function of peeling off the organic matter covering the metal particles. The metal particles from which the organic matter has been peeled off lose their dispersion stability and aggregate, which promotes contact and fusion between the particles, forming a dense metal film. There are no particular limitations on the functional group that has a high affinity for metal particles, and those containing nitrogen atoms in particular have a high affinity for metal particles and are preferably used as sintering accelerators. The sintering accelerator containing nitrogen atoms is not particularly limited, and examples thereof include aromatic amines such as metaphenylenediamine and diaminodiphenylmethane; imidazole compounds such as 2-ethyl-4-methylimidazole, 2-methylimidazole, 1,2-dimethylimidazole, and 1-cyanoethyl-2-methylimidazole; imidazoline compounds such as 2-methylimidazoline; dihydrazide compounds such as sebacic acid dihydrazide and isophthalic acid dihydrazide; amine adducts such as Amicure PN-23 and Amicure MY-24; and dicyandiamide. Among these, dicyandiamide is preferably used because of its high sintering-accelerating effect. The sintering accelerator may be used alone or in combination of two or more.
[0047] The bonding material of the present invention may contain a dispersant from the viewpoint of preventing aggregation. Commercially available dispersants include, for example, Solsperse 9000, Solsperse 12000, Solsperse 17000, Solsperse 20000, Solsperse 21000, Solsperse 24000, Solsperse 26000, Solsperse 27000, Solsperse 28000, Solsperse 32000, Solsperse 35100, Solsperse 54000, and Solsix 250 (all manufactured by Lubrizol Japan Co., Ltd.), EFKA 4008, EFKA 4009, EFKA 4010, EFKA 4015, EFKA 4046, EFKA 4047, EFKA 4060, EFKA 4080, EFKA 7462, EFKA 4020, EFKA 4050, EFKA 4055, EFKA 4400, and EFKA 4401, EFKA 4402, EFKA 4403, EFKA 4300, EFKA 4330, EFKA 4340, EFKA 6220, EFKA 6225, EFKA 6700, EFKA 6780, EFKA 6782, EFKA8503 (all manufactured by Fuka Additives Co., Ltd.), Ajisper PA111, Ajisper PB711, Ajisper PB821, Ajisper PB822, Ajisper PN411, Famex L-12 (all manufactured by Ajinomoto Fine-Techno Co., Ltd.), DisperBYK101, DisperBYK102, DisperBYK106, DisperBYK108, DisperBYK111, DisperBYK116, DisperBYK130, DisperBYK140, DisperBYK142, DisperBYK145, DisperBYK161, DisperBYK162, DisperBYK163, DisperBYK164, DisperBYK166, DisperBYK167, DisperBYK168, DisperBYK169, DisperBYK200, DisperBYK201, DisperBYK202, DisperBYK203, DisperBYK204, DisperBYK205, DisperBYK206, DisperBYK207, DisperBYK208, DisperBYK209, DisperBYK300, DisperBYK301, DisperBYK302, DisperBYK303, DisperBYK304, DisperBYK305, DisperBYK306, DisperBYK307, DisperBYK308, DisperBYK309, DisperBYK310, DisperBYK311, DisperBYK312, DisperBYK313, DisperBYK314, DisperBYK315, DisperBYK316, DisperBYK317, DisperBYK318, DisperBYK319, DisperBYK320, DisperBYK321, DisperBYK322, DisperBYK323, Disper Examples of such compounds include DisperBYK170, DisperBYK171, DisperBYK174, DisperBYK180, DisperBYK182, DisperBYK192, DisperBYK193, DisperBYK2000, DisperBYK2001, DisperBYK2020, DisperBYK2025, DisperBYK2050, DisperBYK2070, DisperBYK2155, DisperBYK2164, BYK220S, BYK300, BYK306, BYK320, BYK322, BYK325, BYK330, BYK340, BYK350, BYK377, BYK378, BYK380N, BYK410, BYK425, and BYK430 (all manufactured by BYK Japan Co., Ltd.). The content of the dispersant is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, based on 100% by mass of the bonding material, in order to prevent residues during sintering. In order to prevent aggregation, the content is preferably 0.1% by mass or more.
[0048] <Joining method and article> The article of the present invention comprises a first member and a second member bonded together with a sintered body formed from the bonding material of the present invention. Since the bonding material is a conductive paste, the bonded article can be expanded into an electric circuit on an electronic substrate, such as an IC chip, and an electronic component mounted thereon. The article of the present invention can be obtained by a manufacturing method including a step of applying a bonding material to at least a first member, and a step of contacting a second member with the bonding material on the first member and then firing the resulting material. The types of the first and second members are not particularly limited, and may be the same or different. The members may be appropriately processed by corona treatment, plating, or the like to increase the bonding strength.
[0049] Examples of the first and second members include metal members, electronic elements, plastic materials, and ceramic materials. Among these, it is preferable to join metal members together, a metal member and a semiconductor element, or a metal member and an LED element. That is, it is preferable to sandwich the bonding material of the present invention between metal members, between a metal member and a semiconductor element, or between a metal member and an LED element, heat it to remove organic solvents and coating materials, and melt at least a portion of the metal particles to form a sintered body, and then bond the metal members, the metal member and the semiconductor element, or the metal member and the LED element with the sintered body.
[0050] Examples of the metal member include a copper substrate, a gold substrate, and an aluminum substrate. Examples of electronic elements include semiconductor elements and LED elements. As semiconductor elements, for example, in addition to silicon and germanium, gallium arsenide, gallium phosphide, and cadmium sulfide are used. Examples of LED elements include aluminum, silicon nitride, diamond, graphite, yttrium oxide, and magnesium oxide, and power device elements such as silicon carbide and gallium nitride can also be used. Examples of plastic materials include polyimide, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, and polyethylene naphthalate. Examples of ceramic materials include glass and silicon.
[0051] The method for applying the bonding material is not particularly limited as long as it can be applied uniformly onto the member. Examples of the method include various printing methods such as screen printing, flexographic printing, offset printing, gravure printing, metal mask printing, and gravure offset printing, and a dispenser method.
[0052] The firing conditions in the bonding step can be appropriately adjusted, but examples of the firing conditions include atmospheric pressure, a nitrogen atmosphere, a vacuum, a pressurized or reducing atmosphere, and a temperature of 200 to 300°C. Examples of the baking device include a hot air oven, an infrared oven, a reflow oven, a microwave oven, and a light baking device. In the case of a light baking device, the type of light to be irradiated is not particularly limited, and examples thereof include a mercury lamp, a metal halide lamp, a chemical lamp, a xenon lamp, a carbon arc lamp, and a laser light. These devices can be used alone or in combination as appropriate. EXAMPLES
[0053] The present invention will be described in more detail below using examples and comparative examples, but the technical scope of the present invention is not limited thereto. Parts and % represent parts by mass and % by mass.
[0054] <Production of metal particles> (Silver particles 1) A separable 4-neck flask was fitted with a cooling tube, a thermometer, a nitrogen gas inlet tube, and a stirrer. 200 parts of toluene and 22.3 parts of silver hexanoate were charged while stirring at room temperature under a nitrogen atmosphere to obtain a 0.5M solution, and then 2.3 parts of diethylaminoethanol (0.2 mol times per 1 mol of metal) and 2.8 parts of oleic acid (0.1 mol times per 1 mol of metal) were added as dispersants and dissolved. Then, 73.1 parts of a 20% solids concentration succinic acid dihydrazide (hereinafter, SUDH) aqueous solution (2 mol times hydrazide groups per 1 mol of metal) were dropped as a reducing agent, and the liquid color changed from pale yellow to dark brown. The temperature was raised to 40 ° C. to further promote the reaction, and the reaction was allowed to proceed. After standing and separating, the aqueous phase was removed to remove excess reducing agent and impurities, and distilled water was added to the toluene layer several times, followed by repeated washing and separation to obtain a toluene dispersion of nanoparticles. 2.4 parts of hexanoic acid was added to this toluene dispersion, and a poor solvent was further added, followed by repeating centrifugation and washing, and then drying to obtain Silver Powder 1. The average particle size of Silver Powder 1 was 10 nm.
[0055] (Silver particles 2) Silver Powder 2 was obtained in the same manner as Silver Powder 1, except that 22.3 parts of silver hexanoate was replaced with 19.5 parts of silver butanoate, and 2.4 parts of hexanoic acid was added to the toluene dispersion with 1.9 parts of butanoic acid. The average particle size of Silver Powder 2 was 10 nm.
[0056] (Silver particles 3) Silver Powder 3 was obtained in the same manner as Silver Powder 1, except that 22.3 parts of silver hexanoate was replaced with 25.1 parts of silver octanoate, and 2.4 parts of hexanoic acid was added to the toluene dispersion with 3.0 parts of octanoic acid. The average particle size of Silver Powder 3 was 10 nm.
[0057] (Silver particles 4) Silver Powder 4 was obtained in the same manner as Silver Powder 1, except that 2.8 parts of oleic acid was changed to 2.3 parts of myristic acid. The average particle size of Silver Powder 4 was 10 nm.
[0058] (Silver particles 5) Silver Powder 5 was obtained in the same manner as Silver Powder 1, except that the amount of hexanoic acid added to the toluene dispersion was changed from 2.4 parts to 9.8 parts. The average particle size of Silver Powder 5 was 10 nm.
[0059] (Silver particles 6) Silver Powder 6 was obtained in the same manner as in Example 1, except that 2.4 parts of hexanoic acid was added to the toluene dispersion, and 5.9 parts of oleic acid was added. The average particle size of Silver Powder 6 was 10 nm.
[0060] (Silver particles 7) A separable 4-neck flask was fitted with a cooling tube, a thermometer, a nitrogen gas inlet tube and a stirrer, and 200 parts of toluene and 22.3 parts of silver hexanoate were charged while stirring at room temperature under a nitrogen atmosphere to obtain a 0.5M solution, and then 2.3 parts of diethylaminoethanol (0.2 mol times per mol of metal) and 2.8 parts of oleic acid (0.1 mol times per mol of metal) were added as dispersants and dissolved. Then, 10.0 parts of hydrazine monohydrate (2 mol times per mol of metal) was added, and the reaction proceeded vigorously. Next, 100 parts of distilled water was added, left to stand and separated, and the aqueous layer was removed to remove precipitates, excess reducing agent and impurities, and distilled water was further added to the toluene layer several times, followed by repeated washing and separation to obtain a toluene dispersion of nanoparticles. 2.4 parts of hexanoic acid were added to this toluene dispersion, and a poor solvent was further added, followed by repeated centrifugation and washing, and drying to obtain silver powder 7. The average particle size of silver powder 7 was 20 nm.
[0061] (Silver particle A) A separable 4-neck flask was fitted with a cooling tube, a thermometer, a nitrogen gas inlet tube and a stirrer, and 200 parts of toluene and 22.3 parts of silver hexanoate were charged under a nitrogen atmosphere at room temperature while stirring to obtain a 0.5M solution, and then 2.3 parts of diethylaminoethanol (0.2 mol times per mol of metal) and 1.2 parts of hexanoic acid (0.1 mol times per mol of metal) were added as dispersants and dissolved. Then, 73.1 parts of a succinic acid dihydrazide aqueous solution with a solid content concentration of 20% (2 mol times the hydrazide group per mol of metal) were dropped as a reducing agent, and the liquid color changed from pale yellow to dark brown. The temperature was raised to 40°C to further promote the reaction, and the reaction was allowed to proceed. After standing and separating, the aqueous phase was removed to remove excess reducing agent and impurities, and distilled water was added to the toluene layer several times, followed by repeated washing and separation to obtain a toluene dispersion of nanoparticles. A poor solvent was added to this toluene dispersion, followed by repeated centrifugation and washing, and then drying to obtain silver powder A. The average particle size of silver powder A was 20 nm.
[0062] (Silver particle B) Silver Powder B was obtained in the same manner as Silver Powder A, except that 22.3 parts of silver hexanoate was replaced with 38.9 parts of silver oleate, and 1.2 parts of hexanoic acid was added to the toluene dispersion with 2.8 parts of oleic acid. The average particle size of Silver Powder B was 800 nm.
[0063] (Silver particle C) Silver Powder C was obtained in the same manner as Silver Powder 1, except that 22.3 parts of silver hexanoate was replaced with 16.7 parts of silver acetate, and 2.4 parts of hexanoic acid was added to the toluene dispersion with 1.3 parts of acetic acid. The average particle size of Silver Powder C was 10 nm.
[0064] (Silver particle D) Silver Powder D was obtained in the same manner as Silver Powder 1, except that 22.3 parts of silver hexanoate was replaced with 27.9 parts of silver decanoate, and 2.4 parts of hexanoic acid was added to the toluene dispersion with 3.6 parts of decanoic acid. The average particle size of Silver Powder D was 10 nm.
[0065] (Silver particles E) Silver Powder E was obtained in the same manner as Silver Powder 1, except that 2.8 parts of oleic acid was changed to 2.0 parts of lauric acid. The average particle size of Silver Powder E was 10 nm.
[0066] (Silver particle F) Silver Powder F was obtained in the same manner as Silver Powder 1, except that 2.8 parts of oleic acid was changed to 3.4 parts of erucic acid. The average particle size of Silver Powder F was 10 nm.
[0067] The molar ratios of fatty acid A and fatty acid B coating silver particles 1 to 7 and silver particles A to F were calculated by quantitatively analyzing the volatile components generated by heating the silver particles to 400°C or higher using a GC-MS (QP-5050, manufactured by Shimadzu Corporation) equipped with a pyrolysis injection device. The results are shown in Table 1.
[0068] <Adjustment of bonding material> [Example 1] (Preparation of bonding material 1) A bonding material 1 was obtained by mixing 90.0 parts of silver particles 1, 6.0 parts of Isopar L (manufactured by Exxon Mobil Corp., boiling point 199° C.), and 4.0 parts of Tersolve MTPH (manufactured by Nihon Terpene Chemical Co., Ltd., isobornylcyclohexanol, boiling point 318° C.).
[0069] [Examples 2 to 14, Comparative Examples 1 to 10] (Preparation of Bonding Materials 2 to 24) Bonding materials 2 to 24 were obtained in the same manner as bonding material 1, except that the types and amounts of metal particles, organic solvent, and sintering accelerator were changed to those shown in Table 1.
[0070] <Evaluation of bonding materials> The obtained bonding material was evaluated as follows, and the results are shown in Table 1.
[0071] [viscosity] The viscosity was measured (Pa·s) using an E-type viscometer one minute after the start of rotation after leaving the bonding material at 25°C for one day.
[0072] [Coating suitability] The bonding material was applied to a steel plate under the following conditions, and its coatability was evaluated according to the following criteria. (Coating conditions) Metal mask: 4mm square opening, 50μm thickness (manufactured by Celia Corporation) Metal squeegee: 40mm x 250mm, thickness 1mm (made by Seria Corporation) (Evaluation Criteria) A: The adhesive is evenly attached to the entire opening (4 mm square area). B: The adhesive is attached to part of the opening (within the range of 3 to 3.7 mm square). C: The adhesive is attached to part of the opening (within a 2-3 mm square area). D: The adhesive is attached to an area of the opening that is less than 2 mm square.
[0073] [Joint strength (shear strength)] The bonding material was applied to the substrate 1 under the following coating conditions, and the substrate 2 was attached. The temperature was then raised from 25°C to 300°C at 5°C per minute, and sintered at 300°C for 120 minutes in an air atmosphere to obtain an article, which was used as a test piece. The thickness of the bonding material when applied was 50 μm, the same as the plate thickness of the metal mask used. (Coating conditions) Metal mask: 4mm square opening, 50μm thickness (manufactured by Celia Corporation) Metal squeegee: 40mm x 250mm, thickness 1mm (made by Seria Corporation) Substrate 1: Copper plate 1.3cm x 1.3cm (thickness 2mm) Substrate 2: Si chip 5mm x 5mm (thickness 300μm)
[0074] The bond strength of the obtained test pieces was measured before and after the following thermal cycle test. The bond strength was measured using a universal bond tester (4000 series, manufactured by DAGE JAPAN Co., Ltd.) by fixing the substrate 1 and pushing the interface between the substrate 1 and the sintered body toward the substrate 2 at a height of 100 μm at a speed of 500 μm / s, and measuring the strength [MPa] at which the bond was broken. (heat cycle test) The test piece was held at -40°C for 30 minutes and then held at 150°C for 30 minutes, which constituted one treatment cycle. This treatment was repeated 500 times.
[0075] [Table 1]
[0076] The abbreviations in Table 1 are as follows: Isopar L: Exxon Mobil, boiling point 199°C MTPH: Nihon Terpene Chemical Co., Ltd., isobornylcyclohexanol, boiling point 318°C DICY7: Mitsubishi Chemical Corporation, JER Cure DICY7, sintering accelerator
[0077] As shown in Table 1, the bonding material of the present invention, which is a combination of two fatty acids having specific carbon numbers and two organic solvents having specific boiling points, has sinterability at a relatively low temperature of about 300°C and has excellent bonding strength before and after thermal cycles. In particular, Example 1, in which the boiling point difference between fatty acid A and solvent C and the boiling point difference between fatty acid B and solvent D were small, showed superior bonding strength before and after thermal cycles compared with Examples 3, 4 and 8. Comparing Example 1 with Examples 6 and 7, Example 1, in which the mass ratio of organic solvent C and organic solvent D (mass of organic solvent C / mass of organic solvent D) was within the range of 1 to 3, showed superior bonding strength before and after thermal cycles. Comparing Example 1 with Examples 13 and 14, Example 1, in which the molar ratio of fatty acid A and fatty acid B (moles of fatty acid A / moles of fatty acid B) was within the range of 2 to 5, showed superior bonding strength before and after thermal cycles. Comparing Example 1 with Example 5, Example 1 showed superior bonding strength before and after the thermal cycle. This is presumably because silver particles 1 contained in Example 1 have a smaller average particle size and a more uniform particle size distribution, which improves coatability by reducing viscosity and reduces voids by densely arranging the particle sizes.
[0078] On the other hand, the bonding strength before and after the thermal cycle was insufficient in Comparative Examples 1 and 2, which did not contain a high boiling point solvent. This is presumably because the amount of voids increased due to the absence of a high boiling point solvent. Comparative Example 3, which contains two types of metal particles coated with a single coating material, had insufficient bonding strength before and after the thermal cycle. This is presumably because one metal particle was coated with a type of fatty acid, so the silver particles coated with a coating material with a lower boiling point started sintering first, and after the coating film hardened, the silver particles coated with the other coating material with a higher boiling point sintered, which prevented gas from being discharged smoothly and formed many voids inside the film. In Comparative Examples 4 to 10, which used inappropriate combinations of coating materials and organic solvents, the bonding strength before and after thermal cycling was insufficient. This is presumably because gas was not discharged smoothly and many voids were formed inside the film.
Claims
1. A bonding material comprising metal particles coated with a fatty acid and an organic solvent, The metal particles are each coated with a fatty acid, the fatty acid including fatty acid A having 4 to 8 carbon atoms and fatty acid B having 14 to 20 carbon atoms, at least a part of the particle surface of the metal particle being coated with the fatty acid, the metal particles are silver nanoparticles, The bonding material, wherein the organic solvent includes organic solvent C having a boiling point of 170° C. or more and 230° C. or less, and organic solvent D having a boiling point of 300° C. or more and 350° C. or less.
2. 2. The bonding material according to claim 1, wherein a molar ratio of fatty acid A to fatty acid B (moles of fatty acid A / moles of fatty acid B) is 0.5 to 30.
3. The bonding material according to claim 1 or 2, wherein the mass ratio of organic solvent C to organic solvent D (mass of organic solvent C / mass of organic solvent D) is 1 to 3.
4. The bonding material according to any one of claims 1 to 3, wherein the boiling point of the fatty acid A is a temperature within ±0 to ±20°C of the boiling point of the organic solvent C.
5. The bonding material according to any one of claims 1 to 4, wherein the boiling point of the fatty acid B is a temperature within ±0 to 50°C of the boiling point of the organic solvent D.
6. The metal particles are a reduction product obtained by reducing a silver compound using a carbodihydrazide represented by the following formula (1) or a polybasic acid polyhydrazide represented by the following formula (2). The bonding material according to any one of claims 1 to 5. 【Chemistry 1】 [In formula (2), R represents an n-valent polybasic acid residue.]
7. An article in which metal members are bonded together, a metal member and a semiconductor element, or a metal member and an LED element are bonded together with a sintered body formed from the bonding material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Joint material and joint method using the same
JP2015225842A
Joining material and joining method using same
JP2018059192A
Bonding paste and article joined with the bonding paste
JP2018172728A
Method for producing metal particle dispersion, conductive ink using metal particle dispersion produced by such method, and conductive coating film
WO2007043664A1
Bonding material and bonding method in which said bonding material is used
WO2013108408A1